PTH-245 Endoscopic removal of buried bumper pegs. outcome of a novel technique from a district general hospital. (22nd June 2015) - Robertson, H; Harding, S; McLaughlin, S
Abstract : Introduction: Buried Bumper syndrome is a known complication following PEG tube insertion. Migration of the internal bumper into the gastrostomy tract may lead to tube blockage or abdominal wall infection. Several removal techniques have been described including balloon push or pull traction, needle-knife technique, foreceps pull, snare technique and external traction. We describe the outcome of a case series from our institution using a novel technique described in 2010 by a German group 1 which utilises a metal rod. To our knowledge, outcomes following this procedure have not yet been reported. Method: We maintain a prospective endoscopy database. Electronic case notes were reviewed. Demographic, procedural, safety and outcome data in all patients were recorded. Results: 15 procedures of buried bumper PEG removal were undertaken in 12 patients during the period July 2010 to December 2014 by the same endoscopist. Mean age; 67(range 38–90). 10 were male (82%). 11 of 12 (92%) were considered to lack capacity to consent. Indications for initial PEG insertion were: stroke (6), brain injury (3), Huntington's Chorea (1), Cerebral Palsy (1), Multiple Sclerosis (1). 12 of 15 (80%) buried PEG bumpers were removed using the device. The procedure was unsuccessful in 3 (20%) patients who subsequently underwent a mini-laparotomy. 3 (20%) patients developed aspiration pneumonia following the procedure at a mean of 5 days (range 2–8 day). 1 of these was from the surgical group and 2 from the endoscopically managed group. The 2 in the endoscopy group were successfully managed with antibiotics. In 3 patients (20%) the procedure was performed as a day case. 12 (80%) required inpatient stay following the procedure. Mean length of stay was 7 days. (Range 1–22 days.) 1 patient developed bleeding from the old PEG site post procedure and required endoscopic intervention. 30 day mortality in the group that underwent surgery was 33% (1 patient). Cause of death was aspiration pneumonia. In the endoscopically managed group, the 30 day mortality was 0%. One year mortality was 33% for the surgical group and 8% in the endoscopically managed group. Conclusion: Our data suggests that this procedure is safe and effective, particularly when compared to the surgical alternative in this high risk group. The success rate of this procedure was high, suggesting that by utilising this technique, surgery can be avoided in the majority of patients with buried bumper syndrome. Disclosure of interest: None Declared. Reference: Binnebossal M, Klink CD, et al . Endoscopic Removal of Buried Bumper. Department of Surgery. RWTH Aachen University: Endoscopy. 2010:42:E17–18